Theory of Peplau – a critical analysis of its application on the treatment of a person with diagnosis of anxiety - Zélia Maria de Sousa Araújo Santos; Vera Lúcia Mendes de Oliveira; Lorita Marlena Freitag Pagliuca (Rev Rene)
In the present paper we opted for the critical analysis of a study previously carried out by ourselves as an activity in the context of our M.D. course, which resulted in a text entitled “Nursing and Interpersonal Interaction – basis for intervention in the diagnosis of anxiety”. At that moment, applying a nursing theory on a practical situation was enough. To reach the analysis we now propose, we took the guidelines set by American nurses Chinn and Kramer in their book Theory and Nursing – a systematic approach as references. We also opted for the theoretical references set by some philosophic presuppositions by Karl Popper e Bachelard. In the clinical situation studied, we observed that the application of the four phases of the Theory of Peplau was decisive for a client to meet his needs. However, this theory must be applied with some restriction on unconscious clients due to the limitations that such a clinical state imposes to interactive action, which is the major characteristic of the theory referred.